Remediasi Miskonsepsi Peserta Didik Pada Materi Optik Dengan Teknik CRI Modifikasi Melalui Model Learning Cycle 5E - Haeroni Haeroni; Susilawati Susilawati; Satutik Rahayu (Department of Physics Education, Universitas Mataram, 2019)
This research aimed to find out the level of misconceptions and the effect of 5e learning cycle model. This research was a pre-experimental with pre-test and post-test design. The research population was all of the eleven grade students of Senior High School 1 Mataram consisted of 8 classes. Sampling was done by cluster random sampling technique and obtained students of class XI MIPA 5. StudentsÃ¢â¬â¢ misconceptions have been identified by modification of Certainty of Response Index technique and remediated with 5e learning cycle model. The result of data analysis showed that students experience misconceptions with the various level that was high, medium, and low. The misconception of students before remediation was 44% in the concept of reflection and 34% in the concept of refraction, meanwhile, after remediation, the misconceptions on the concept of reflection was 6% and the concept of refraction was 9%. As a result, 5e learning cycle model could decrease the level of misconception. It showed that 5e learning cycle model was effective to decrease the level of misconception. From the paired sample t-test, it was found that tcount= 8,042 and ttable=2,045, because of tcount > ttable there was an effect of 5e learning cycle model on a misconception.